2010
DOI: 10.1590/s1413-86702010000100015
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile paracoccidioidomycosis in urban area: report of two cases

Abstract: We present two cases of juvenile form of paracoccidioidomycosis (PCM), a systemic mycosis frequently found in rural areas, whose prognosis is poor in children and young adults. They are a 14-year-old boy and a 25-year-old woman, both residents in an urban area in São Paulo -Brazil, without any history of travelling to an endemic area. They have been admitted to the hospital due to fever, weight loss and lymphadenopathy. The diagnosis was confirmed by serologic and histopathologic study. Patients have recovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
1
0
2
Order By: Relevance
“…Male rural workers and/or those who carry out activities related to the country field such as earthwork, gardening and vegetable loading, are the people most affected by chronic PCM 6,10,12,21,25‐30 . However, in the last years there has been an increase in the occurrence of PCM in the urban area 31 . With regard to women, our study showed a predominance of patients from rural areas and housewives, ranging from 40 to 50 years old, similar to male prevalence.…”
Section: Discussionsupporting
confidence: 61%
“…Male rural workers and/or those who carry out activities related to the country field such as earthwork, gardening and vegetable loading, are the people most affected by chronic PCM 6,10,12,21,25‐30 . However, in the last years there has been an increase in the occurrence of PCM in the urban area 31 . With regard to women, our study showed a predominance of patients from rural areas and housewives, ranging from 40 to 50 years old, similar to male prevalence.…”
Section: Discussionsupporting
confidence: 61%
“…Skin lesions occur in 30% to 50% of cases and are mucosal nodules, vegetations, or ulcers (muriform stomatitis). In one‐quarter of cases, usually children and adolescents, the presentation is of acute or subacute disease, which is disseminated and progresses rapidly, with high mortality .…”
Section: Fungal Diseasesmentioning
confidence: 99%
“…É possível que o fato da maioria dos pacientes ser procedente da zona urbana tenha contribuído para o atraso diagnóstico, já que os inquéritos epidemiológicos mostram maior prevalência da doença em zona rural. Entretanto, vem se observando aumento de focos de infecção periurbano, com descrição de casos em área urbana sem antecedente de viagem a áreas endêmicas (5,6,7). Dessa forma, mesmo em região urbana, a paracoccidioidomicose deve ser lembrada no diagnóstico diferencial relativo à quadros de linfoma símile, de osteomielite, de ascite e icterícia de etiologia a esclarecer.…”
Section: Discussão -Estudo Clínico-laboratorialunclassified
“…No Brasil, há casos descritos em todas as regiões, com maior incidência no sudeste (1,2). Tradicionalmente descrita como doença típica de regiões rurais, vem se observando aumento de focos de infecção periurbano, com descrição de casos em área urbana sem antecedente de viagem a áreas endêmicas (5,6,7). A distribuição epidemiológica heterogênea no território brasileiro se deve às diferenças das características sócio econômicas regionais, fluxo migratório, diferentes estruturas de serviço de saúde e de características ambientais e biológicas do agente etiológico e do hospedeiro (4).…”
unclassified